MOF-derived bimetallic sulfide-MXene composite material microsphere as well as preparation method and application thereof

By using MOF-derived bimetallic sulfide-MXene composite microspheres, the problem of volume expansion and side reactions of sodium ion battery anode material during charging and discharging is solved, and higher cycle life and electrochemical performance are achieved.

CN119725444AActive Publication Date: 2025-03-28CHINA UNIV OF MINING & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411863515.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-28
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The existing sodium ion battery negative electrode materials expand volume during charging and discharging, generate intermediate products and side reactions, resulting in a decrease in cycle stability and life.

Method used

The MOF-derived bimetallic sulfide-MXene composite microspheres are used to achieve high conductivity and excellent sodium storage cycle stability through nitrogen-doped carbon in situ modification and two-dimensional nanosheets.

Benefits of technology

It effectively avoids volume expansion and side reactions, and improves the cycle life and electrochemical performance of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725444A_ABST
    Figure CN119725444A_ABST
Patent Text Reader

Abstract

The invention discloses MOF-derived bimetallic sulfide-MXene composite material microspheres and a preparation method and application thereof.The preparation method of the microspheres comprises the steps that MXene nanosheets are weighed according to the mass-to-volume ratio of (1-3): (4-10) and added into a mixed solution, the MXene nanosheets are fully dissolved, and a solution A is obtained; adding cobalt salt and nickel salt with equal molar weight and a composite additive into the solution A, and dispersing to obtain a solution B; transferring the solution B into a reaction kettle, reacting at 150-170 DEG C for 8-12 hours, washing a product after centrifugal precipitation, and carrying out vacuum drying treatment for 8-12 hours to obtain a composite precursor; and putting the composite precursor powder and sulfur powder into a tubular furnace, heating to 500-600 DEG C, carrying out heat preservation reaction, and cooling to obtain the composite material microspheres. The composite material microsphere not only realizes dual regulation and control of nitrogen-doped carbon in-situ modification, but also presents a porous microsphere structure formed by two-dimensional nanosheets, shows good ion conductivity, excellent rate capability and relatively high conductivity in the field of energy storage, and prolongs the cycle life of a sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of composite electrode materials for sodium ion batteries, and in particular to a method for preparing MOF-derived bimetallic sulfide-MXene composite microspheres. The present invention also relates to composite porous microspheres for sodium ion battery electrode materials. Background Art

[0002] As a new type of electrochemical energy storage system, sodium-ion batteries have attracted widespread attention due to their abundant resources, low cost and environmental friendliness. The selection of negative electrode materials is crucial to the performance of sodium-ion batteries. As a promising negative electrode material, transition metal sulfides (TMSs) have been widely studied and applied to sodium-ion batteries due to their rich variety, relatively high theoretical specific capacity and excellent redox reaction reversibility. In particular, these materials use a conversion reaction mechanism to store sodium, which can provide a relatively stable capacity during the charge and discharge process.

[0003] However, sodium-ion battery negative electrode materials based on transition metal sulfides face many challenges in practical applications. First, these materials undergo significant volume expansion during the charge and discharge process, leading to the collapse and pulverization of the electrode structure, which seriously affects the cycle stability of the battery. Secondly, transition metal sulfides may generate some intermediate products during the conversion reaction. The dissolution of these products in the electrolyte not only reduces the efficiency of the battery, but may also trigger a "shuttle effect", further leading to rapid capacity decay and a sharp drop in cycle life. In addition, side reactions that may accompany the charge and discharge process (such as electrolyte decomposition, gas generation, etc.) will also have a negative impact on the performance of the battery, further exacerbating the above problems.

[0004] In view of the above problems and background, how to overcome volume expansion, inhibit side reactions and improve cycle life has become the key to improving the performance of sodium-ion batteries. In order to deal with these problems, researchers are exploring a variety of approaches, including structural optimization of materials, surface modification, and design of composite materials, in order to achieve higher energy density and longer service life. Summary of the invention

[0005] In view of the above-mentioned problems, the purpose of the present invention is to provide a MOF-derived bimetallic sulfide-MXene composite microsphere and its preparation method and application. The composite microsphere not only realizes the dual regulation of nitrogen-doped carbon in-situ modification, but also presents a porous microsphere structure composed of two-dimensional nanosheets, which exhibits good ion conductivity, excellent rate capability and high conductivity in the field of energy storage, thereby extending the cycle life of sodium ion batteries.

[0006] A MOF-derived bimetallic sulfide-MXene composite microsphere, the preparation method of which comprises:

[0007] S1: Weigh MXene nanosheets according to a mass volume ratio of 1-3:4-10 and add them to the mixed solution to fully dissolve them to obtain solution A;

[0008] S2: adding equimolar amounts of cobalt salt, nickel salt and composite additive to solution A, and ultrasonically dispersing to obtain solution B;

[0009] S3: moving solution B into a reaction kettle, placing it in an oven at 150-170°C for reaction for 8-12 hours, washing the product after centrifugal precipitation, and vacuum drying the product for 8-12 hours to obtain a composite precursor of a nickel-cobalt-based binary metal organic framework and MXene;

[0010] S4: Put the composite precursor powder and sulfur powder into a tubular furnace, heat them to 500-600°C at a certain heating rate and keep them warm for 1-4 hours, and then cool them to room temperature to obtain a MOF-derived bimetallic sulfide-MXene composite material.

[0011] Furthermore, in step S1, the mixed solution is deionized water, ethanol and N,N-dimethylformamide in a volume ratio of 1:1:1.

[0012] Furthermore, in step S1, hydrogen fluoride is used as an etchant to prepare MXene nanosheets, and the method is as follows: HF is placed in a reaction container, and then Ti3AlC2 raw material is slowly added at a volume mass ratio of 20-50:1-3, the mixture is magnetically stirred at 30-50°C for 10-24h, and then the precipitated product is collected by centrifugation and washed with deionized water until neutral, and then freeze-dried to obtain accordion-shaped multilayer MXene; the dried multilayer MXene is dispersed in deionized water at a volume mass ratio of 1:50-200 to obtain solution C, solution C is ultrasonicated in an ice bath for 30-60min, and then centrifuged at 3000-5000rpm / min for 1-3h, and the suspension after centrifugation is freeze-dried to obtain a few-layer or single-layer MXene nanosheet.

[0013] Furthermore, in step S2, the cobalt salt includes one of cobalt nitrate, cobalt chloride or cobalt sulfate, and the nickel salt includes one of nickel nitrate, nickel chloride and nickel sulfate.

[0014] Furthermore, in step S2, the composite additive is polyvinyl pyrrolidone and 2,5-dihydroxyterephthalic acid in a molar ratio of 1:6-7.

[0015] Furthermore, in step S2, the molar ratio of the cobalt nickel salt to the composite additive is 40:7-8.

[0016] Furthermore, in step S4, the composite precursor powder and the sulfur powder are placed at two ends of the porcelain boat respectively, and the front end containing the sulfur powder is close to the air inlet of the pure argon gas of the tubular furnace.

[0017] Furthermore, in step S4, the heating rate is 1-2°C min -1 .

[0018] The second object of the present invention is to provide an application of the MOF-derived bimetallic sulfide-MXene composite microspheres in sodium ion batteries.

[0019] The third object of the present invention is to provide a MOF-derived bimetallic sulfide-MXene composite microsphere, comprising a porous microsphere structure composed of two-dimensional MXene nanosheets, and also comprising bimetallic nickel cobalt sulfide nanoparticles intercalated between the MXene nanosheet layers.

[0020] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0021] The beneficial effects of the present invention are:

[0022] 1. Due to the synergistic effect, the bimetallic nickel-cobalt sulfide of the present invention not only has higher conductivity, more active sites, and higher electrochemical activity than single metal sulfide; and the mixed valence state and electronic synergistic effect of the bimetallic ions increase its reaction activity, improve its sodium storage capacity, and have excellent sodium storage cycle stability;

[0023] 2. The metal organic framework (MOFs) of the present invention is an ideal template for preparing nanoporous metal sulfides and trace nitrogen and carbon doping. Due to its highly ordered pore structure and rich organic components, a nitrogen-doped carbon MOFs precursor with high specific surface area and porosity can be obtained by high-temperature carbonization, and the product after sulfurization can still retain the porous nanostructure of the MOFs precursor;

[0024] 3. The porous microsphere structure composed of two-dimensional nanosheets of the present invention can not only effectively avoid the agglomeration of bimetallic nickel cobalt sulfide nanoparticles and two-dimensional MXene nanosheets, but also exhibit a larger specific surface area, rapid ion transfer and a stable structure, and can effectively alleviate the volume expansion of the material during charging and discharging, reduce the occurrence of side reactions, and extend the cycle life of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0026] Figure 1 The SEM images of the materials in Example 1 and Comparative Examples 1 to 2 of the present invention are shown in Figure 1, wherein (a) is a layered MXene obtained by HF etching; (b) is a prepared MOF-derived bimetallic sulfide; (c) is a prepared MOF-derived bimetallic sulfide-MXene composite material;

[0027] Figure 2 TEM image of the MOF-derived bimetallic sulfide-MXene composite material in Example 1 of the present invention;

[0028] Figure 3 Schematic diagram of the charge-discharge cycle performance of MXene, MOF-derived bimetallic sulfide, and MOF-derived bimetallic sulfide-MXene composite material in Example 1 and Comparative Examples 1-2 of the present invention;

[0029] Figure 4 Schematic diagram of the rate performance of MXene, MOF-derived bimetallic sulfide, and MOF-derived bimetallic sulfide-MXene composite material in Example 1 and Comparative Examples 1-2 of the present invention;

[0030] Figure 5 This is a long cycle performance diagram of the MXene material in Example 3 of the present invention;

[0031] Figure 6 This is a long cycle performance diagram of the MOF-derived bimetallic sulfide-MXene composite material in Example 3 of the present invention. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] In this example, a MOF-derived bimetallic sulfide-MXene composite microsphere was prepared by the following steps:

[0035] Step 1: Preparation of MXene nanosheets

[0036] MXene nanosheets were prepared using hydrogen fluoride as an etchant, and the method was as follows: 20 mL of HF was placed in a 50 mL plastic beaker, and then 1 g of Ti3AlC2 raw material was slowly added, the mixture was magnetically stirred at 40°C for 24 h, and then the precipitated product was collected by centrifugation and washed with deionized water until neutral, and then freeze-dried to obtain accordion-shaped multilayer MXene; the dried multilayer MXene was dispersed in 100 mL of deionized water, and subjected to ice bath ultrasonic treatment for 45 min, and then the solution was centrifuged at 3500 rpm / min for 2 h, and the suspension after centrifugation was freeze-dried to obtain few-layer MXene nanosheets.

[0037] Step 2: Preparation of composite precursor

[0038] 10 mg of the prepared few-layer MXene nanosheet powder was added to 30 mL of a mixed solution of deionized water, ethanol and N, N-dimethylformamide (DMF) in a volume ratio of 1:1:1, and stirred vigorously for 30 min to fully dissolve it. Then, 0.75 mmol of equimolar amounts of Ni(NO3)2·6H2O and Co(NO3)2·6H2O, 1.5 g of polyvinyl pyrrolidone (PVP, MW40000) additive and 50 mg of 2,5-dihydroxyterephthalic acid (H4-DHBDC) solvent were added respectively, and ultrasonic dispersion was performed at room temperature. Then, the mixed solution was transferred to the polytetrafluoroethylene liner of the reactor. The sealed reactor was placed in an oven at 170°C for 12 h, and the centrifugal precipitate was rinsed alternately with deionized water and ethanol several times. Then, the product was vacuum dried at 80°C for 12 h to obtain a composite material of MOFs-derived precursor and MXene.

[0039] Step 3. Preparation of MOF-derived bimetallic sulfide-MXene composites

[0040] 200 mg of composite precursor powder and 100 mg of sulfur powder were placed at the two ends of the porcelain boat, with the front end containing sulfur powder close to the pure argon inlet of the tube furnace. -1 The temperature was raised to 600 °C and kept at that temperature for 2 h, and then cooled to room temperature to obtain a MOF-derived bimetallic sulfide-MXene composite material.

[0041] MXene 10mg

[0042] NiS 68mg

[0043] Co3S4 91mg

[0044] The MOF-derived bimetallic sulfide-MXene composite material prepared by the above method has a porous microsphere structure, wherein the microsphere is composed of two-dimensional nanosheet stacking.

[0045] In actual use, the MOF-derived bimetallic sulfide-MXene composite microspheres prepared by the present invention can be used as the negative electrode material of the sodium ion battery, the MOF-derived bimetallic sulfide-MXene composite material is used as the negative electrode material of the sodium ion battery, the electrolyte is 1.0M NaPF6 dissolved in dimethyl ether (DME), Whatman GF / C glass fiber is used as the diaphragm, the sodium metal sheet is used as the counter electrode (half-cell), and sodium vanadium phosphate Na3V2(PO4)3 is used as the positive electrode (full cell) to test the electrochemical performance.

[0046] The MOF-derived bimetallic sulfide-MXene composite microsphere preparation method of this embodiment prepares a composite material of bimetallic nickel cobalt sulfide nanoparticles intercalated with MXene two-dimensional nanosheets. The composite material has a porous microsphere structure composed of two-dimensional nanosheets, which can not only effectively avoid the agglomeration of bimetallic nickel cobalt sulfide nanoparticles and two-dimensional MXene nanosheets, but also alleviate the volume expansion during charging and discharging. In addition, the bimetallic nickel cobalt sulfide has more active sites and higher electrochemical activity due to synergistic effects, and MXene has good ionic conductivity and electrical conductivity, so that the prepared composite material has excellent sodium storage cycle stability.

[0047] Comparative Example 1

[0048] This comparative example prepared a MXene nanosheet by following the steps below:

[0049] Step 1: Preparation of MXene nanosheets

[0050] MXene nanosheets are prepared using hydrogen fluoride as an etchant, and the method is as follows: 20 mL of hydrogen fluoride is placed in a 50 mL plastic beaker, and then 1 g of Ti3AlC2 raw material is slowly added, the mixture is magnetically stirred at 40°C for 24 hours, and then the precipitated product is collected by centrifugation and washed with deionized water until neutral, and then freeze-dried to obtain accordion-shaped multilayer MXene; the dried multilayer MXene is dispersed in 100 mL of deionized water, and subjected to ice bath ultrasonic treatment for 30-60 minutes, and then the solution is centrifuged at 3500 rpm / min for 1 hour, and the suspension after centrifugation is freeze-dried to obtain few-layer or single-layer MXene nanosheets.

[0051] MXene 10mg

[0052] NiS 0mg

[0053] Co3S4 0mg

[0054] MXene was used as the negative electrode material of sodium-ion batteries, the electrolyte was 1.0 M NaPF6 dissolved in dimethyl ether (DME), Whatman GF / C glass fiber was used as the separator, and sodium metal sheet was used as the counter electrode to test the electrochemical performance.

[0055] Comparative Example 2

[0056] In this comparative example 2, a MOF-derived bimetallic sulfide was prepared by the following steps:

[0057] Step 1: Ni 0.5 Co 0.5 - Preparation of MOFs

[0058] 0.75mmol Ni(NO3)2·6H2O and 0.75mmol Co(NO3)2·6H2O, 1.5g polyvinylpyrrolidone (PVP, MW40000) and 50mg 2,5-dihydroxyterephthalic acid (H4-DHBDC) were dissolved in 30mL of mixed solvent (deionized water = ethanol = DMF = 10mL), and ultrasonicated for 30min at room temperature. Then, the clear and uniform solution was transferred to the polytetrafluoroethylene liner of the reactor. After the reactor was sealed, it was placed in a 160℃ blast oven and kept at high temperature and high pressure for 12h. After cooling to room temperature, the light green precipitate was collected by centrifugation and washed alternately with DMF, deionized water and ethanol for several times. Finally, the centrifuged product was placed in a vacuum drying oven at 80℃ for drying.

[0059] Step 2: Preparation of MOF-derived bimetallic sulfides

[0060] The Ni obtained in step 1 0.5 Co 0.5 -MOFs precursor and sublimated sulfur powder were weighed in a mass ratio of 2:1, and the precursor and sublimated sulfur powder were placed at both ends of an alumina porcelain boat, and then the porcelain boat was transferred to a high-temperature tube furnace. In order to fully sulfide Ni 0.5 Co 0.5 -MOFs precursor, place the front end containing sulfur powder close to the pure argon inlet. Then, -1 The mixture was heated to 600°C at a heating rate of 100 °C and kept at that temperature for 2 hours, and then cooled to room temperature to obtain the product.

[0061] MXene 0g

[0062] NiS 68mg

[0063] Co3S4 91mg

[0064] MOF-derived bimetallic sulfides were used as negative electrode materials for sodium-ion batteries. The electrolyte was 1.0 M NaPF6 dissolved in dimethyl ether (DME), Whatman GF / C glass fiber was used as the separator, and metal sodium sheet was used as the counter electrode to test the electrochemical performance.

[0065] The MOF-derived bimetallic sulfide-MXene composite microspheres prepared in Example 1 of the present invention have a porous microsphere structure composed of two-dimensional nanosheets, and bimetallic nickel cobalt sulfide nanoparticles are distributed on the two-dimensional MXene. Figure 1 a is a SEM image of layered MXene obtained by HF etching in Comparative Example 1; Figure 1 b is the SEM image of MOF-derived bimetallic sulfide porous microspheres in Comparative Example 2; Figure 1 c is the SEM image of the MOF-derived bimetallic sulfide-MXene composite material prepared in Example 1. Figure 2 TEM image of the prepared MOF-derived bimetallic sulfide-MXene composite material. Figure 2 In the figure, metal sulfide nanoparticles of different sizes are seen riveted onto the two-dimensional MXene nanosheets ( Figure 2 ac), Figure 2 In the enlarged image of b, it can be seen that MXene presents a lamellar structure similar to two-dimensional graphene, on which metal sulfide nanoparticles are loaded. The distribution of bimetallic nickel-cobalt sulfide nanoparticles on the MXene two-dimensional substrate not only facilitates electron transport, but also effectively prevents the restacking of two-dimensional MXene nanosheets, giving full play to its surface activity. Figure 2 The clear lattice fringes of 0.232 nm in HRTEM of d correspond to the (400) crystal plane of Co3S4 phase in the composite material.

[0066] Figure 3 The results show that MXene, MOF-derived bimetallic sulfides, and MOF-derived bimetallic sulfide-MXene composites can be used for high current 1A -1 The charge-discharge cycle performance under the condition of 100 cycles shows that the charge-discharge capacity of MOF-derived bimetallic sulfide and MOF-derived bimetallic sulfide-MXene composite is significantly higher than that of single MXene. After 100 cycles, the reversible specific capacity of the composite is 438.7 mAh g -1 The corresponding capacity retention rate is as high as 91.4%, which is a significant improvement over the 82.1% of bimetallic sulfide (NiS / Co3S4); from the enlarged Coulomb efficiency embedding diagram, it can be observed that the Coulomb efficiency value of the composite material electrode during the charge and discharge process is more stable, indicating that its cycle stability is also significantly higher than that of the other two materials MXene and MOF-derived bimetallic sulfide.

[0067] Figure 4 The rate performance of MXene, MOF-derived bimetallic sulfide, and MOF-derived bimetallic sulfide-MXene composites is shown in Figure 2. The rate performance of the composite electrode is 0.1, 0.2, 0.5, 1.0, 2.0, and 5.0 A g -1 The discharge specific capacities at the current densities are 550.7, 532.6, 513.1, 479.9, 442.6 and 387.6 mAh g -1 , although at 2.0A g -1 and 5.0A g -1 However, when the current density is restored to 0.1A -1 When the specific capacity of the composite material can be restored to 575.6 mAh g -1 , which is much higher than that of bimetallic sulfide electrode (487.8 mAh g -1 ) and MXene electrodes (87.2 mAh g -1 ), indicating that the MOF-derived bimetallic sulfide-MXene composites have excellent rate performance and reversibility, as well as fast-response sodium-ion storage kinetic behavior.

[0068] Example 2

[0069] This embodiment 2 relates to a MOF-derived bimetallic sulfide-MXene composite microsphere, which includes a porous microsphere structure composed of two-dimensional nanosheets, and also includes bimetallic nickel cobalt sulfide nanoparticles intercalated between the MXene sheets, and the composite material is prepared by the above-mentioned method for preparing MOF-derived bimetallic sulfide-MXene composite microspheres for sodium ion battery negative electrode materials.

[0070] Example 3

[0071] In this example, a MOF-derived bimetallic sulfide-MXene composite microsphere was prepared by the following steps:

[0072] Step 1: Preparation of MXene nanosheets

[0073] MXene nanosheets were prepared using hydrogen fluoride as an etchant, and the method was as follows: 50 mL of HF was placed in a 100 mL plastic beaker, and then 2 g of Ti3AlC2 raw material was slowly added, the mixture was magnetically stirred at 45°C for 24 h, and then the precipitated product was collected by centrifugation and washed with deionized water until neutral, and then freeze-dried to obtain accordion-shaped multilayer MXene; the dried multilayer MXene was dispersed in 100 mL of deionized water, and subjected to ice bath ultrasonic treatment for 45 min, and then the solution was centrifuged at 5000 rpm / min for 1 h, and the suspension after centrifugation was freeze-dried to obtain few-layer MXene nanosheets.

[0074] Step 2: Preparation of composite precursor

[0075] 15 mg of the prepared few-layer MXene nanosheet powder was added to 50 mL of a mixed solution of deionized water, ethanol and N, N-dimethylformamide (DMF) in a volume ratio of 1:1:1, and stirred vigorously for 30 min to fully dissolve it. Then, 1 mmol of equimolar amounts of Ni(NO3)2·6H2O and Co(NO3)2·6H2O, 2 g of polyvinylpyrrolidone (PVP, MW40000) additives and 70 mg of 2,5-dihydroxyterephthalic acid (H4-DHBDC) solvent were added, respectively, and ultrasonically dispersed at room temperature. Then, the mixed solution was transferred to the polytetrafluoroethylene liner of the reactor. The sealed reactor was placed in an oven at 170°C for 12 h, and the centrifugal precipitate was rinsed alternately with deionized water and ethanol several times. Then, the product was vacuum dried at 80°C for 12 h to obtain a composite material of MOFs-derived precursor and MXene.

[0076] Step 3. Preparation of MOF-derived bimetallic sulfide-MXene composites

[0077] 200 mg of composite precursor powder and 100 mg of sulfur powder were placed at the two ends of the porcelain boat, with the front end containing sulfur powder close to the pure argon inlet of the tube furnace. -1 The heating rate was increased to 550 °C and kept at this temperature for 4 h, and then cooled to room temperature to obtain a MOF-derived bimetallic sulfide-MXene composite material.

[0078] MXene 10mg

[0079] NiS 68mg

[0080] Co3S4 91mg

[0081] The MOF-derived bimetallic sulfide-MXene composite material prepared by the above method has a porous microsphere structure, wherein the microsphere is composed of two-dimensional nanosheet stacking.

[0082] In actual use, the MOF-derived bimetallic sulfide-MXene composite microspheres prepared by the present invention can be used as the negative electrode material of the sodium ion battery, the MOF-derived bimetallic sulfide-MXene composite material is used as the negative electrode material of the sodium ion battery, the electrolyte is 1.0M NaPF6 dissolved in dimethyl ether (DME), Whatman GF / C glass fiber is used as the diaphragm, the sodium metal sheet is used as the counter electrode (half-cell), and sodium vanadium phosphate Na3V2(PO4)3 is used as the positive electrode (full cell) to test the electrochemical performance.

[0083] Figure 5 The cycle performance of the MXene nanosheets prepared in Example 3 shows that the MXene electrode has a good cycling performance at 0.2Ag. -1 The discharge capacity after 100 cycles at a current density of 1.38 was only 78.2 mAh g -1 , then at 1Ag -1 At a high current density, the discharge capacity decays to 63.1 mAh g after 650 cycles. -1 .

[0084] Figure 6 The MOF-derived bimetallic sulfide-MXene composite electrode prepared in Example 3 was subjected to a maximum current density of 5Ag. -1 The long-term cycle performance diagram under . It can be seen that after 200 cycles, the specific capacity of the composite electrode began to rise slowly and showed a continuous activation process. After 1450 cycles, the specific capacity reached 456.9 mAh g -1 , the corresponding capacity retention rate is as high as 98.7%, and the stable coulombic efficiency value is close to 100%. The excellent long-term cycling performance of MOF-derived bimetallic sulfide-MXene composite electrode should be attributed to the unique porous microsphere structure, which makes full use of the abundant active sites on the two-dimensional MXene nanosheets, and the metal sulfide particles anchored on the nanosheets are effectively restricted, which buffers the volume expansion of the electrode material during the sodium insertion / de-sodiumization process, thereby enhancing its cycling stability.

[0085] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A MOF-derived bimetallic sulfide-MXene composite microsphere, characterized in that: The preparation method thereof comprises: S1: Weigh MXene nanosheets according to a mass volume ratio of 1-3:4-10 and add them to the mixed solution to fully dissolve them to obtain solution A; S2: adding equimolar amounts of cobalt salt, nickel salt and composite additive to solution A to disperse and obtain solution B; S3: moving solution B into a reactor, reacting at 150-170°C for 8-12 hours, washing the product after centrifugal precipitation, and vacuum drying the product for 8-12 hours to obtain a composite precursor of a nickel-cobalt-based binary metal organic framework and MXene; S4: Put the composite precursor powder and sulfur powder into a tubular furnace, heat them to 500-600°C at a certain heating rate and keep them warm for 1-4 hours, and then cool them to room temperature to obtain MOF-derived bimetallic sulfide-MXene composite microspheres.

2. A MOF-derived bimetallic sulfide-MXene composite microsphere according to claim 1, characterized in that: In step S1, the mixed solution is deionized water, ethanol and N,N-dimethylformamide in a volume ratio of 1:1:

1.

3. A MOF-derived bimetallic sulfide-MXene composite microsphere according to claim 1, characterized in that: In step S1, hydrogen fluoride is used as an etchant to prepare MXene nanosheets, and the method is as follows: HF is placed in a reaction container, and then Ti3AlC2 raw material is slowly added at a volume mass ratio of 20-50:1-3, the mixture is magnetically stirred at 30-50°C for 10-24h, and then the precipitated product is collected by centrifugation and washed with deionized water until neutral, and then freeze-dried to obtain accordion-shaped multilayer MXene; the dried multilayer MXene is dispersed in deionized water at a volume mass ratio of 1:50-200 to obtain solution C, solution C is ultrasonicated in an ice bath for 30-60min, and then centrifuged at 3000-5000rpm / min for 1-3h, and the suspension after centrifugation is freeze-dried to obtain a few-layer or single-layer MXene nanosheet.

4. A MOF-derived bimetallic sulfide-MXene composite microsphere according to claim 1, characterized in that: In step S2, the cobalt salt includes one of cobalt nitrate, cobalt chloride or cobalt sulfate, and the nickel salt includes one of nickel nitrate, nickel chloride and nickel sulfate.

5. A MOF-derived bimetallic sulfide-MXene composite microsphere according to claim 1, characterized in that: In step S2, the composite additive is polyvinyl pyrrolidone and 2,5-dihydroxyterephthalic acid in a molar ratio of 1:6-7.

6. A MOF-derived bimetallic sulfide-MXene composite microsphere according to claim 1, characterized in that: In step S2, the molar ratio of the cobalt nickel salt to the composite additive is 40:7-8.

7. A MOF-derived bimetallic sulfide-MXene composite microsphere according to claim 1, characterized in that: In step S4, the composite precursor powder and the sulfur powder are placed at two ends of the porcelain boat respectively, and the front end containing the sulfur powder is close to the air inlet of the pure argon gas of the tubular furnace.

8. A MOF-derived bimetallic sulfide-MXene composite microsphere according to claim 1, characterized in that: In step S4, the heating rate is 1-2°C min -1 .

9. Application of the MOF-derived bimetallic sulfide-MXene composite microspheres according to claim 1 in sodium ion batteries.

10. The MOF-derived bimetallic sulfide-MXene composite microsphere of claim 1, comprising a porous microsphere structure composed of two-dimensional MXene nanosheets, and also comprising bimetallic nickel-cobalt sulfide nanoparticles intercalated between the MXene nanosheet layers.

Citation Information

Patent Citations

  • Two-dimensional layered composite film and preparation method and application thereof

    CN113083036A

  • Cobalt nickel sulfide-MXene electrode material for supercapacitor and preparation method of cobalt nickel sulfide-MXene electrode material

    CN113764203A

  • Hollow microspherical MXene / Sn-S / PANI composite material as well as preparation method and application thereof

    CN117890438A

  • Preparation Method and Application for Metal Sulfide Hollow Microspheres with Enriched Sulfur Vacancies

    US20220246934A1